The effect of a new coronavirus infection (COVID-19) on clinical and radiological manifestations in patients with comorbidity of respiratory tuberculosis, HIV-infection and opportunistic lung diseases: prospective study design - Vladimir Yu. Mishin; Anastasiia V. Mishina; Dmitriy A. Lezhnev; Aleksandr L. Sobkin; Natalya V. Sergeeva; Aleksandr S. Kononets; Irina Yu. Babaeva (ZAO "Consilium Medicum", 2022)
Aim. To study the features of clinical and radiological manifestations and diagnosis of COVID-19, respiratory tuberculosis and opportunistic lung infections (OIL) coinfection in patients with late stages of HIV-infection with immunodeficiency. Materials and methods. The study included 29 patients with COVID-19 coinfection, respiratory tuberculosis and opportunistic lung infections in the late stages of HIV-infection with immunodeficiency (group 1) and 29 patients similar in all parameters without COVID-19 (group 2). All patients were underwent clinical and laboratory, radiation and bronchological examination, and microbiological, immunological, molecular genetic, cytological and histological examination of diagnostic material of the respiratory tract, cerebrospinal and pleural fluid, blood, urine and feces to identify pathogens of coinfection. Statistical data processing was carried out using the Microsoft Office Excel 2010 program with the calculation of the average in the group and the standard error of the average, confidence interval. Results. It has been established that co-infection with COVID-19, respiratory tuberculosis and opportunistic lung infections in patients with late stages of HIV-infection with immunodeficiency is manifested by a pronounced intoxication syndrome, bronchopulmonary manifestations and symptoms of damage to other organs and systems, which is due to the generalization of tuberculosis with extrapulmonary lesions and the development of opportunistic lung infections, as in patients without COVID-19. A computed tomogram of the chest organs with this coinfection visualizes the syndrome of dissemination, the syndrome of adenopathy and the syndrome of pathology of the pulmonary pattern, represented by the compaction of interstitial tissue in the frosted glass type, which is associated with the simultaneous layering of various pathologies, which complicates their differential diagnosis. This determines the similarity of clinical and radiological manifestations of COVID-19 coinfection, respiratory tuberculosis and opportunistic lung infections in patients with late-stage HIV-infection with immunodeficiency, as in patients without COVID-19. This requires complex microbiological and molecular genetic research methods to identify specific pathogens for the appointment of timely treatment. Conclusion. Patients with COVID-19 coinfection, respiratory tuberculosis and opportunistic lung infections in the late stages of HIV-infection with immunodeficiency pose a high risk of infection in a healthy population, taking into account their social maladaptation and non-adherence to examination and treatment. This requires an active diagnosis of COVID-19 in all patients with respiratory tuberculosis and HIV-infection who are registered in the office of anti-tuberculosis care for HIV-infected in an anti-tuberculosis dispensary, for emergency isolation and treatment.